Improved canine and human visceral leishmaniasis immunodiagnosis using combinations of synthetic peptides in enzyme-linked immunosorbent assay. - Míriam Maria Costa; Marcos Penido; Mariana Silva dos Santos; Daniel Doro; Eloísa de Freitas; Marilene Susan Marques Michalick; Gabriel Grimaldi; Ricardo Tostes Gazzinelli; Ana Paula Fernandes (Public Library of Science (PLoS), 2012)
BACKGROUND: Zoonotic visceral leishmaniasis (VL) is a severe infectious disease caused by protozoan parasites of the genus Leishmania and the domestic dogs are the main urban parasite reservoir hosts. In Brazil, indirect fluorescence antibody tests (IFAT) and indirect enzyme linked immunosorbent assay (ELISA) using promastigote extracts are widely used in epidemiological surveys. However, their sensitivity and specificity have often been compromised by the use of complex mixtures of antigens, which reduces their accuracy allowing the maintenance of infected animals that favors transmission to humans. In this context, the use of combinations of defined peptides appears favorable. Therefore, they were tested by combinations of five peptides derived from the previously described Leishmania diagnostic antigens A2, NH, LACK and K39. METHODOLOGY/PRINCIPAL FINDINGS: Combinations of peptides derived A2, NH, LACK and K39 antigens were used in ELISA with sera from 44 human patients and 106 dogs. Improved sensitivities and specificities, close to 100%, were obtained for both sera of patients and dogs. Moreover, high sensitivity and specificity were observed even for canine sera presenting low IFAT anti-Leishmania antibody titers or from asymptomatic animals. CONCLUSIONS/SIGNIFICANCE: The use of combinations of B cell predicted synthetic peptides derived from antigens A2, NH, LACK and K39 may provide an alternative for improved sensitivities and specificities for immunodiagnostic assays of VL.